Tourism Village Management Strategy Based On Sense Of Mission And Sense Of Commitment : Study of Community Empowerment in the Management of Teak Timber Hoarding into the Tourism Sector in Benculuk Village, Cluring District, Banyuwangi Regency - Maulana, Akbar; Kholifah R, Emy; Lingga, Juariah (Sadar Wisata: Jurnal Pariwisata, 2023)
This study aims to describe the management of a tourism village in the form of teak wood stockpiling and used as a tourism sector by the Perhutani of Benculuk Village by empowering the surrounding community based on a sense of mission and a sense of commitment. The approach used in this research is descriptive qualitative, and the method of data collection is in the form of interviews conducted with informants who have an interest in managing Djawatan Tourism Village. Analysis of the data obtained was carried out through data collection, data verification, data presentation and drawing conclusions. The results of the study show that the management of teak wood hoarding which is used as a Tourism Village in practical implementation is based on the ACTORS theory and Sense Of Mission and Sense Of Commitment with the aim of minimizing the unemployment rate of the surrounding community. Perhutani has a specific strategy for approaching the community in managing the teak wood stockpiling area so that it becomes a developing and advanced tourism village, so that the surrounding community becomes prosperous, lives happily, and avoids poverty